Delayed administration of carrier marrow can decrease competition on donor stem cells during engraftment and maintain radioprotection of the host - Soper, Brian W.; Lessard, Mark D.; Jude, Craig D.; Schuldt, Adam J.; Barker, Jane E. (Experimental hematology, 2002)
The goal of this study was to determine if competitive pressure was placed on hematopoietic stem cells (HSC) by a coinjected “carrier” population that maintains short-term survival of the host. Our hypothesis was that delayed introduction of “carrier” cells would increase engraftment of donor HSC. Competitive repopulation assays were performed using genetically distinguishable whole bone marrow (BM) populations. Donor BM was competed against carrier BM that was coinjected or injected 3 or 4 days later. Radioprotection with delayed carrier injection also was examined by performing the initial HSC transplantation with Hoechst lo side population (SP) cells. SP HSC incubated with cytokines and BM stroma to stimulate cell cycling before transplantation also were tested using coinjection or delayed carrier administration. Delayed introduction of carrier whole BM increased peripheral expansion of donor whole BM, freshly isolated HSC, or cytokine-stimulated HSC compared to coinjection with carrier cells. A 3-day delay in carrier administration maintained radioprotection in 100% of lethally irradiated recipients of highly enriched HSC, whereas a 4-day delay did not rescue these recipients from death. When recipients are rescued, recovering host marrow can compete against donor HSC unless sufficient donor cells are injected. Delayed introduction of carrier BM significantly increases donor HSC engraftment and peripheral expansion by reducing competition in the host. Competition by a coinjected carrier cell population or recovery of host marrow significantly reduces the therapeutic efficacy of normal or in vitro manipulated donor HSC.